Differential response to rainfall of soil moisture infiltration in permafrost and seasonally frozen ground in Kangqiong small basin on the Qinghai-Tibet Plateau. Issue 3 (17th February 2021) - Cao, Wei; Sheng, Yu; Wu, Jichun; Peng, Erxing
ABSTRACT: This study investigated the differential response to rainfall of soil moisture infiltration in the permafrost area of the downhill slope and in the seasonally frozen ground area of the uphill slope in Kangqiong small basin on the Qinghai-Tibet Plateau. The results show that: (1) influenced by the barrier of the permafrost layer, the suprapermafrost water level in the permafrost area rises significantly, while in the seasonally frozen ground area, the soil moisture infiltration is dominated by lateral flow and downward infiltration. (2) With the thawing of soil, the soil water content in the permafrost area gradually increases to reach a saturated state. Influenced by terrain, soil texture, evapotranspiration and infiltration capacity, the variation in the topsoil moisture content is large in the seasonally frozen ground area. (3) The presence of regional talik groundwater leads to a slight increase in the water level on the uphill slope. In addition to rainfall infiltration, the change in water level on the downhill slope is also affected by talik groundwater, which causes the rapid rise of water level on the down slope.